Peridynamic modeling and simulation of thermo-mechanical de-icing process with modified ice failure criterion - Song, Ying; Li, Shaofan; Zhang, Shuai (Defence technology, 2021)
De-icing technology has become an increasingly important subject in numerous applications in recent years. However, the direct numerical modeling and simulation the physical process of thermo-mechanical deicing is limited. This work is focusing on developing a numerical model and tool to direct simulate the de-icing process in the framework of the coupled thermo-mechanical peridynamics theory. Here, we adopted the fully coupled thermo-mechanical bond-based peridynamics (TM-BB-PD) method for modeling and simulation of de-icing. Within the framework of TM-BB-PD, the ice constitutive model is established by considering the influence of the temperature difference between two material points, and a modified failure criteria is proposed, which takes into account temperature effect to predict the damage of quasi-brittle ice material. Moreover, thermal boundary condition is used to simulate the thermal load in the de-icing process. By comparing with the experimental results and the previous reported finite element modeling, our numerical model shows good agreement with the previous predictions. Based on the numerical results, we find that the developed method can not only predict crack initiation and propagation in the ice, but also predict the temperature distribution and heat conduction during the de-icing process. Furthermore, the influence of the temperature for the ice crack growth pattern is discussed accordingly. In conclusion, the coupled thermal-mechanical peridynamics formulation with modified failure criterion is capable of providing a modeling tool for engineering applications of de-icing technology.